Pomiędzy dzieciństwem a dorosłością – o dorastaniu osób z zespołem Aspergera - Wojciechowska, Aneta (Wydawnictwo Naukowe UAM, 2013)
Adolecence is an extremely diffi cult time for young people. This is the period when they become adults. However, this transition is connected with lots of diffi culties in the area of peer contacts and the acceptance of their physicality. The Asperger syndrome fosters the diffi culties in building interpersonal relationships, their identity as well as in shaping personality itself. The article shows the problems of adolescence coupled with diffi culties arising from Asperger syndrome. It is important to consider if this time is similar for all teenagers, regardless of their developmental capabilities, or whether the diffi culties that result from Asperger syndrome are meaningful in their adolescence period.
Between Childhood and Adulthood – About the Adolescence of People with Asperger Syndrome
Keywords: Asperger syndrome; adolescence